1993
DOI: 10.1002/jsfa.2740630405
|View full text |Cite
|
Sign up to set email alerts
|

Short‐chain fatty acid content and pH in caecum of rats given various sources of carbohydrates

Abstract: The caecal content of short-chain fatty acids (SCFA; acetic, propionic and butyric acid), caecal pH, fermentability and dry matter digestibility (DMD) were examined through balance experiments in rats fed 1 1 various indigestible carbohydrates. The following carbohydrate sources were incorporated into test diets: cellulose, oat husk, wheat bran, oat bran, pea fibre, linseed fibre, low methoxylated (LM)-pectin. guargum, 8-glucans, neosugar and raffinose. The indigestible carbohydrates, except for those in wheat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
106
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(123 citation statements)
references
References 47 publications
16
106
1
Order By: Relevance
“…Indeed an increase in the viscosity of food may have several effects: (a) to slow down the small intestinal transit (Low, 1988;Cherbut et al, 1994); but Cummings et al (1979) did not ®nd any modi®cation of oro-cecal transit time with pectin; (b) to reduce the interaction between food nutrients and digestive enzymes (Flourie  et al, 1984;Cummings et al, 1979; to increase the time for nutrient diffusion, by increasing the thickness of the unstirred water layer (Flourie  et al, 1984;Rydning & Berstad, 1986). This is consistent with the studies which have demonstrated that soluble ®bres could decrease the area under the curve of serum glucose after a duodenal glucose load (Berggren et al, 1993). This is also consistent with our own study: serum insulin response to the test meal, and postprandial serum glucose and triglycerides levels were of less magnitude during the psyllium session than during the placebo one.…”
Section: Inhibition Of Food Intake By Psyllium D Rigaud Et Alsupporting
confidence: 78%
See 1 more Smart Citation
“…Indeed an increase in the viscosity of food may have several effects: (a) to slow down the small intestinal transit (Low, 1988;Cherbut et al, 1994); but Cummings et al (1979) did not ®nd any modi®cation of oro-cecal transit time with pectin; (b) to reduce the interaction between food nutrients and digestive enzymes (Flourie  et al, 1984;Cummings et al, 1979; to increase the time for nutrient diffusion, by increasing the thickness of the unstirred water layer (Flourie  et al, 1984;Rydning & Berstad, 1986). This is consistent with the studies which have demonstrated that soluble ®bres could decrease the area under the curve of serum glucose after a duodenal glucose load (Berggren et al, 1993). This is also consistent with our own study: serum insulin response to the test meal, and postprandial serum glucose and triglycerides levels were of less magnitude during the psyllium session than during the placebo one.…”
Section: Inhibition Of Food Intake By Psyllium D Rigaud Et Alsupporting
confidence: 78%
“…This is also consistent with our own study: serum insulin response to the test meal, and postprandial serum glucose and triglycerides levels were of less magnitude during the psyllium session than during the placebo one. But it could also be related to motor or metabolic actions of psyllium, such as increase in the production of short chain fatty acids by the large bowel in response to the dietary ®bre ingestion (Berggren et al, 1993). This needs further investigation.…”
Section: Inhibition Of Food Intake By Psyllium D Rigaud Et Almentioning
confidence: 99%
“…Purified cellulose has been considered to be a diet's diluent, whereas the other complex carbohydrates are more likely to be extensively degraded by the caecal microflora into SCFA (Juśkiewicz et al, 2005). All SCFA are claimed to act as trophic agents on caecal/colonic epithelium, but butyric seems to be the most and propionic the least efficient (Berggren et al, 1993). Another possible way of increased epithelium proliferation was indicated in a study by Whiteley et al (1996).…”
Section: Discussionmentioning
confidence: 99%
“…Different types of indigestible carbohydrates give rise to different amounts and patterns of CAs during colonic fermentation, and it may therefore be possible to regulate the CA formation by diet. The CAs formed may depend on for example the monomeric composition of the carbohydrates, the type of linkages between the carbohydrate monomers, their solubility and their molecular weight (Berggren et al, 1993;Casterline et al, 1997;Bird et al, 2000;Karppinen et al, 2000;Henningsson et al, 2002Henningsson et al, , 2003Nilsson and Nyman, 2005). Studies examining CA formation have mainly been conducted in vitro by using human faecal inocula, or in vivo using animal models.…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining CA formation have mainly been conducted in vitro by using human faecal inocula, or in vivo using animal models. The rat is the most common model when studying the CA formation in vivo, although there are also some studies available in pigs (Berggren et al, 1993;Roland et al, 1995;Brown et al, 1997;Djouzi and Andrieux, 1997;Bird et al, 2000;Henningsson et al, 2002Henningsson et al, , 2003Nilsson and Nyman, 2005). Studies in man have mainly been performed by measurements of CAs in faeces and have been questioned on the premises that such measurements do not give information regarding the formation of CAs in proximal colon where most of the fermentation actually takes place.…”
Section: Introductionmentioning
confidence: 99%